Esibelekweni: Ingqokelela Yemibongo ngesiXhosa nangesiNgesi - Busakwe, Yenzokuhle (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
My thesis is a collection of poems that is written in isiXhosa and English. It explores African spirituality, my relationship with God, heartache from romantic and platonic relationships. I make use of dual languages because some themes that I write about such as African spirituality I find words that capture their truest emotion in my Xhosa vocabulary, and I cannot find them in English. My poems use the narrative form because it allows me to tell stories through poetry without having to commit my writing to musicality or rhyming that a lyric poetry normally has. My work is shaped by writers such as Kate Beinhemer, Mangaliso Buzani, Amy Saul Zerby, Nontsizi Mgqwethio, Simphiwe Nolutshungu and Oiu Miaojin. Buzani makes use of images and few lines in his writing but still manages to capture a story with brevity. Saul-Zerby makes use of text lingo in some of her poems, and I make use of it to close a gap that I have identified with the books that I was reading that are all written in a formal and serious format. Mgqwetho's poems explore Christianity and African Spirituality which is one of the subjects that my work is exploring too but in a manner that differs. I talk about how they have been my guidance instead of praising their powers like Nontsizi normally does in her poems. Simphiwe Nolutshungu's poems has influenced the structure of my poems. Fairy tales written by writers like Kate helps my writing to bring to life issues that sound too dreamy to be true but have manifested as visions and memories that I cannot wipe out from my conscience. Oiu Miaojin's novel "Last words from Montmantre" I am fascinated by how the writer detail emotions such as vulnerability and heartbreak in his storytelling.
Keywords: Creative writing (Higher education) -- South Africa; Diaries Authorship; Books Reviews; South African essays (English) 21st century; Xhosa poetry 21st century